Optimasi Keamanan Informasi Pendaftaran Event Menggunakan Teknologi Blockchain - Busthomi, Iqbal; Riadi, Imam; Umar, Rusydi (Jurnal Ilmiah FIFO, 2020)
Abstract CV. Nyebar is an IT-based start-up that deals with event data management using a web-based application. The Event system provides account registration services as a Member and Organizer. Members of the Event System must first have an account and log-in to be able to register for the event. The process of registering events so far has not been properly secured. The event registration process will send registrant information, but the information sent has not been secured and validated first, so the Event System is still vulnerable to cyber-attacks including the registration data sniffing attack and Distributed Denial of Service (DDoS) attacks. DDoS attacks are carried out by sending messages and packet requests continuously to the business sector, hosting, social sites originating from bot at one time, resulting in overloaded network servers because of the resources (bandwidth, memory, and CPU usage) they have. the network server is used up. Blockchain which has three techniques/mechanisms including the use of hashes and proof-of-work mechanisms which can be an alternative security for event registration information because it can maintain information security, data consistency, and DDoS attacks. Keyword: Web Application, Distributed Denial of Service (DDoS), Blockchain Abstrak CV. Nyebar merupakan start-up berbasis IT yang bergelut dibidang pengelolaan data event menggunakan sebuah aplikasi berbasis web. Sistem Event menyediakan layanan pendaftaran akun sebagai Member dan Organizer. Member dari Sistem Event harus memiliki akun dan log-in terlebih dahulu untuk mendaftar sebuah event. Proses pendaftaran event sejauh ini belum diamankan dengan baik. Proses pendaftaran event akan mengirimkan informasi pendaftar, namun informasi yang dikirimkan belum diamanakan dan divalidasi terlebih dahulu, sehingga Sistem Event masih rentan akan serangan siber diantaranya adalah serangan sniffing data pendaftaran dan serangan Distributed Denial of Service (DDoS). Serangan DDoS dilakukan dengan mengirimkan pesan dan permintaan paket secara terus menerus kepada sektor bisnis, hosting, situs sosial yang berasal dari bot dalam satu waktu, sehingga mengakibatkan server jaringan menjadi overload karena sumber daya (bandwith, memory, dan CPU usage) yang dimiliki server jaringan habis terpakai. Blockchain yang memiliki dua teknik/mekanisme antara lain adalah penggunaan hash dan mekanisme proof-of-work, yang dapat menjadi alternatif pengamanan informasi pemdaftaran event karena dapat menjaga keamanan informasi, kekonsistenan data, dan serangan dari DDoS. Keyword: Aplikasi Web, Distributed Denial of Service (DDoS), Teknologi Blockchain